Rigid multipodal platforms for metal surfaces - Valášek, Michal; Lindner, Marcin; Mayor, Marcel (Beilstein Journal of Nanotechnology, 2016)
In this review the recent progress in molecular platforms that form rigid and well-defined contact to a metal surface are discussed. Most of the presented examples have at least three anchoring units in order to control the spatial arrangement of the protruding molecular subunit. Another interesting feature is the lateral orientation of these foot structures which, depending on the particular application, is equally important as the spatial arrangement of the molecules. The numerous approaches towards assembling and organizing functional molecules into specific architectures on metal substrates are reviewed here. Particular attention is paid to variations of both, the core structures and the anchoring groups. Furthermore, the analytical methods enabling the investigation of individual molecules as well as monomolecular layers of ordered platform structures are summarized. The presented multipodal platforms bearing several anchoring groups form considerably more stable molecule–metal contacts than corresponding monopodal analogues and exhibit an enlarged separation of the functional molecules due to the increased footprint, as well as restrict tilting of the functional termini with respect to the metal surface. These platforms are thus ideally suited to tune important properties of the molecule–metal interface. On a single-molecule level, several of these platforms enable the control over the arrangement of the protruding rod-type molecular structures (e.g., molecular wires, switches, rotors, sensors) with respect to the surface of the substrate.
Keywords: multivalent anchoring; protruding structure; spatial arrangement; tripodal platform